Mekanisme Psikologis Pembelajaran Transformatif Menuju Kesadaran Kritis pada Orang Dewasa: Literature Review - Yoan Ramadhani; Miranti Arum Yuningsih (Pusat Riset dan Inovasi Nasional, 2026)
Transformative learning is an adult learning approach that emphasizes profound changes in how individuals understand themselves, their experiences, and their social environment. This process involves not only the acquisition of knowledge but also changes in perspectives, identity, and critical consciousness. Although transformative learning has been widely discussed in the literature, studies integrating the psychological mechanisms underlying the transformation process remain limited. This study aims to synthesize empirical and theoretical findings regarding the psychological mechanisms of transformative learning leading to critical consciousness among adults. A literature review method was employed by examining scientific publications retrieved from Google Scholar and ResearchGate between 2021 and 2025. The selection process focused on studies addressing transformative learning, disorienting dilemmas, cognitive dissonance, critical reflection, cognitive schema restructuring, identity transformation, and critical consciousness. The findings indicate that transformative learning occurs through an interconnected sequence of processes beginning with cognitive dissonance triggered by experiences that challenge existing assumptions. This is followed by critical reflection, which facilitates cognitive schema restructuring and perspective transformation, ultimately contributing to identity transformation and the development of critical consciousness. In addition to cognitive factors, emotional experiences were found to play an important role in encouraging reflection and the construction of new meanings. These findings suggest that transformative learning is a multidimensional process involving the interaction of cognitive, emotional, social, and identity-related dimensions. The study highlights the importance of designing adult learning experiences that encourage critical reflection, foster adaptive identity development, and strengthen critical consciousness in responding to personal and societal changes.